1981
DOI: 10.1159/000260529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Different Strontium Salts on Dental Caries in the Rat

Abstract: Strontium as chloride, oxide, nitrate, fluoride, sulphate, and lactate salts was fed to rats given a cariogenic diet, via the drinking water. The dose of strontium given to each rat was 50 mg Sr/1 after weaning and 5.0 μg Sr/10 g body weight when given by oesophageal intubation during the suckling period. The lowest caries scores were seen in rats receiving strontium fluoride, and to a lesser extent in those receiving strontium chloride. All other salts used had little or no effect on caries. Greater reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Similar results effects were obtained reported on rats exposed to Sr posteruptively by Olson et al [1978]. Curzon and Spector [1981] studied the effects of different Sr salts at [Sr] = 50 ppm on rat caries reduction and concluded that SrF2 was most effective, mainly because of its [F] = 22 ppm. Other salts varied in their effectiveness based on their bioavailability.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Similar results effects were obtained reported on rats exposed to Sr posteruptively by Olson et al [1978]. Curzon and Spector [1981] studied the effects of different Sr salts at [Sr] = 50 ppm on rat caries reduction and concluded that SrF2 was most effective, mainly because of its [F] = 22 ppm. Other salts varied in their effectiveness based on their bioavailability.…”
supporting
confidence: 85%
“…Animal studies on the effects Sr in preventing caries have been equivocal as no effects [Johnson and Hein, 1953;Olson et al, 1978], an increase [Hunt andNavia, 1972, 1975;Joseph et al, 1977] or a decrease [Losee and Adkins, 1968;Gedalia et al, 1975;Meyerowitz et al, 1979;Ashrafi et al, 1980;Curzon and Spector, 1981;Curzon, 1988] in caries incidence were have been reported. Generalization of overall Sr effects, however, is unjustified as differences depending on the dose and time of administration (pre-and/or post-eruptively) or the combined administration of Sr and F need to be analyzed for separately.…”
Section: Animal Caries Studiesmentioning
confidence: 99%
“…It has been suggested that the reduction in caries attributed to Sr (Curzon and Spector, 1981) may be a combined Sr and fluoride effect, resulting in improved crystallinity of carbonated apatite (Featherstone et al, 1983). Crystalline effects cannot be detected by the present test procedure.…”
Section: Resultsmentioning
confidence: 72%
“…Although the effect of F is not dependent on the presence of Sr, and neither does the effect of Sr appear to depend on F, a combination of Sr and F in plaque may have an advantage over either ion alone. The two ions have a synergistic effect in reducing the dissolution of hydroxyapatite when present in acid solutions (Dedhiya et al, 1974), and have been reported to provide greater protection in in vitro caries models (Herbison and Handelman, 1975;Luoma et al, 1986) and in rat studies (Meyerowitz et al, 1979;Curzon and Spector, 1981;Luoma et al, 1984) when present together than when tested separately. Both ions are taken up by carious enamel, the combination producing a superior remineralizing effect (Little and Baer, 1979;Featherstone et al, 1985).…”
Section: Introductionmentioning
confidence: 99%